Ultra-processed food consumption is associated with variations in daily routines in elementary schoolchildren during the COVID-19 pandemic in Chile - Fretes, Gabriela; Corvalán, Camila; Economos, Christina D.; Wilson, Norbert L.W.; Cash, Sean B. (Cambridge University Press, 2023)
Objective: To assess the association between child ultra-processed food (UPF) consumption and home-school learning environment characteristics during school closures due to the COVID-19 pandemic in schoolchildren with low- and middle-income in Chile.